224 Epimural microbiota and rumen epithelial gene expression in healthy and liver-abscessed animals. (30th November 2020) - Abbas, Waseem; Lindholm-Perry, Amanda K; Keel, Brittney N; Wells, James E; Hales, Kristin; Knoell, Allison; Paz, Henry A; Fernando, Samodha
Abstract: Different dietary and feed additive strategies have been developed to reduce the liver abscess in feedlot cattle, but liver abscesses are still a major problem in beef production. We have limited knowledge about how rumen microbial communities interact with host epithelial gene expression in healthy and liver-abscessed animals. The objective of this study was to investigate the associations between the rumen content associated and rumen epimural microbiome and epithelial gene expression in liver-abscessed and healthy animals. To this end, we collected the ruminal contents and tissue samples from healthy (N=30; score=0, steers n=19 and heifers n=11) and liver-abscessed (N=30; score=A+, steers n=21 and heifers n=9) feedlot cattle at harvest. The bacterial community compositions in the ruminal contents and papillae were evaluated via 16S rDNA sequencing of the V4 region using the Illumina MiSeq platform. Additionally, total RNA was extracted from rumen epithelial tissues and sequenced using the Illumina NextSeq platform. The permutational analysis (PERMANOVA) on Bray Curtis distances matrices showed the microbial community in the ruminal contents was significantly different (P< 0.001) from the bacterial community observed in rumen papillae. The ruminal contents contained a higher abundance of Bacteroidetes and Proteobacteria while papillae contained higher abundance of Firmicutes. The epimural microbiota was different (P< 0.01) between healthy and liver abscessed animals while ruminal contents microbiome was not different between the two groups. The DeSeq2 algorithm identified differentially expressed genes (221) related to MAPK, NF-kappa B signaling pathway, immune and inflammatory response in liver-abscessed animals. Additionally, a wide range of epimural bacterial taxa were correlated (-0.52 to 0.67) with differentially expressed genes. These data demonstrate the interaction between epimural microbiota and the host and its effect on liver abscesses, and indicate the need to study the epimural microbiome for its impact on liver abscesses in feedlot cattle. USDA is an equal opportunity provider and employer.